Terrestrial OH nightglow measurements during the Rosetta flyby. Issue 13 (14th July 2015) - Migliorini, A.; Gérard, J. C.; Soret, L.; Piccioni, G.; Capaccioni, F.; Filacchione, G.; Snels, M.; Tosi, F.
Abstract We present a study of the terrestrial hydroxyl nightglow emissions observed with the Visible and Infrared Thermal Imaging Spectrometer on board the Rosetta mission. During these observations, the OH Δv = 1 and 2 sequences were measured simultaneously. This allowed investigating the relative population of the v = 1 to 9 vibrational levels by using both sequences. In particular, the relative population of the vibrational level v = 1 is determined for the first time from observations. The vibrational population decreases with increasing vibrational quantum number. A good agreement is found with a recent model calculation assuming multiquantum relaxation for OH(v) quenching by O2 and single‐quantum relaxation for OH(v) by N2.